Chapter Per una tipologia delle scritture prodotte e conservate dalle cancellerie signorili - Senatore, Francesco (Reti Medievali E-Book, 2023)
There is no real difference between the records of the biggest rural Lords and those of the Principalities in late medieval Italy. Both ones had a more or less organised chancery and produced documents in chancery form. Their archival history too is similar. The paper proposes and discusses the documentary typology of the documents made by and for the Lords. The Empire, the Holy See, the Kingdoms may have influenced the form of seigneurial litterae patentes and clausae, although there were individual nuances. The other documents, as registers and other chancery books were influenced by different regional traditions.